Facile approach for constructing TEV insertions to probe protein structure in vivo - Elysa Brown; Stanley Maloy (BioTechniques)
The tobacco etch virus (TEV) protease has been used as a tool to examine protein structure in vivo. TEV cleavage sites (TEVcs) have been introduced via cloning into unique restriction sites or random transposon mutagenesis. We describe a facile, efficient method for introducing TEVcs at precise locations in a gene to test specific predictions about protein structure. The method uses the λ Red recombination system to construct seamless, in-frame insertions of the TEVcs at any desired location within an open reading frame (ORF). The system was tested using the multifunctional PutA protein Salmonella enterica sv. Typhimurium. The first step involved insertion of a chloramphenicol resistance (CamR) cassette with a transcriptional terminator at the desired location. A second swap then replaces the CamR insertion with the TEVcs. Placing a copy of the lac operon downstream of the putA gene provides a simple counterselection for replacement of the CamR insertion and also provides a reporter gene for monitoring transcription of the mutated gene.